Arsenic exposure on bovine health and environmental pollution with special emphasis on groundwater system in Manipur - DEVI, H TIKENBALA; GHOSH, CHHOTAN KUMAR; DATTA, BAKUL KUMAR; DASGUPTA, RAJU; MUKHOPADHAYAY, SUNIT KUMAR; MANDAL, TAPAN KUMAR; SARKAR, SAMAR; CHAKRABORTY, ANIMESH KUMAR (The Indian Journal of Animal Sciences, 2010)
There was high arsenic content in soil, drinking water and grass in Manipur suggestive of environmental pollution by the arsenic contaminant, which was due to groundwater containing arsenic more than the permissible limit. The cattle of 2 zones in Manipur were selected for the present study, i.e. Kakching block in Thoubal district as exposed zone and Kamjong block in Ukhrul district as control zone. The arsenic content in faeces, urine, milk, hair and serum in cattle of exposed zone were higher compared to control zone. High concentration of arsenic in milk indicated the presence of arsenic in food-chain. It suggests the testing of milk and hair for arsenic concentration that could be considered as biomarker to assess the arsenic exposure.